Being With Cyril: Can Heideggerian language do justice to the experience of supporting a severely disabled individual? (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This paper offers an account of experiences felt when supporting a severely disabled individual. It discusses the dilemmas that these experiences raised and attempts to explain them using Heideggerian language: Is this individual a 'Dasein' or simply another entity, did this individual 'leap ahead' and open up the author's possibilities of being?
Keywords: Disability; being; existential; Heidegger; psychotherapy; leaping in; leaping ahead